2017
DOI: 10.1007/s12551-017-0295-1
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from a tarantula: new insights into muscle thick filament and myosin interacting-heads motif structure and function

Abstract: The tarantula skeletal muscle X-ray diffraction pattern suggested that the myosin heads were helically arranged on the thick filaments. Electron microscopy (EM) of negatively stained relaxed tarantula thick filaments revealed four helices of heads allowing a helical 3D reconstruction. Due to its low resolution (5.0 nm), the unambiguous interpretation of densities of both heads was not possible. A resolution increase up to 2.5 nm, achieved by cryo-EM of frozen-hydrated relaxed thick filaments and an iterative h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 128 publications
2
33
0
Order By: Relevance
“…We used mant-ATP single turnover experiments to calculate the fraction of myosin heads hydrolyzing ATP at their normal basal (~0.03 s -1 ) rate versus their SRX (~0.003 s -1 ) rate. 24,41,42 A recent publication by Anderson et al 24 showed that the SRX corresponds to a folded-back (sequestered) state of myosin, possibly the IHM described previously 30,31 . Our studies show that the mutant 25-hep HMMs show a much greater fraction of myosin heads in the fast phase compared to WT 25-hep HMM, consistent with our hypothesis that these mutations disrupt the myosin intramolecular interactions that sequester heads in the SRX inactive state.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…We used mant-ATP single turnover experiments to calculate the fraction of myosin heads hydrolyzing ATP at their normal basal (~0.03 s -1 ) rate versus their SRX (~0.003 s -1 ) rate. 24,41,42 A recent publication by Anderson et al 24 showed that the SRX corresponds to a folded-back (sequestered) state of myosin, possibly the IHM described previously 30,31 . Our studies show that the mutant 25-hep HMMs show a much greater fraction of myosin heads in the fast phase compared to WT 25-hep HMM, consistent with our hypothesis that these mutations disrupt the myosin intramolecular interactions that sequester heads in the SRX inactive state.…”
Section: Introductionmentioning
confidence: 93%
“…3a). If the myosin is in an open state, then its mant-nucleotide release rate in the absence of actin is higher (~0.03 s -1 ; 'fast') than that of the sequestered SRX (~0.003 s -1 ; 'slow') 30,41 . Fitting the mant-ATP fluorescence vs time data to a double exponential (equation 1) gives the fraction of myosin in the SRX slow phase.…”
Section: Hcm Mutations On the Myosin Mesa Of 25-hep Hmm Lead To A Gaimentioning
confidence: 99%
See 1 more Smart Citation
“…Dynamic and asymmetric interaction of the two heads in a pair of myosin II molecules forms a myosin interacting-heads motif (IHM) structure. During relaxation, there are two relaxation states of myosin dimers in striated muscles, including human cardiac muscle, depending on IHM interaction: the disordered relaxed (DRX) state and the ordered relaxed or super-relaxed (SRX) state [8,9] ( Figure 2). In the DRX state, the blocked head (BH) docked onto its S2 and actin-binding interface is positioned on the converter domain of the partner free head (FH).…”
Section: Super-relaxed State In the Heartmentioning
confidence: 99%
“…The disordered relaxed (DRX) state and the ordered relaxed or super-relaxed (SRX) state [8,9] (Figure 2). In the DRX state, the blocked head (BH) docked onto its S2 and actin-binding interface is positioned on the converter domain of the partner free head (FH).…”
Section: Super-relaxed State In the Heartmentioning
confidence: 99%